The Role of the NIS (SLC5A5) Gene in Papillary Thyroid Cancer: A Systematic Review - Rafael Martins de Morais; Alaor Barra Sobrinho; Calliandra Maria de Souza Silva; Jamila Reis de Oliveira; Izabel Cristina Rodrigues da Silva; Otávio de Toledo Nóbrega (International Journal of Endocrinology)
Papillary thyroid cancer (PTC) is the most common thyroid malignancy. Genetic and epigenetic alterations play a decisive role in the onset of several human neoplasms. Mutations and polymorphisms are two frequent genetic alterations. Located on chromosome 19 (19p13.11), the NIS SLC5A5 (solute carrier family 5 member 5) gene encodes a highly specialized and efficient 80–90 kDa transmembrane glycoprotein that mediates active transport of iodide from the bloodstream into the follicular cells. Given the highly significant role of NIS in the physiology and the cancer pathogenesis process, this paper’s objective is to provide a comprehensive assessment of the associations between NIS gene and protein with papillary thyroid cancer.